2018
DOI: 10.14738/abr.612.5719
|View full text |Cite
|
Sign up to set email alerts
|

Corruption in Public Procurement in Ghana: societal norm or deviant behaviour?

Abstract: The paper probes corruption in public procurement in Ghana. The research, which focused on Metropolitan, Municipal and District Assemblies (MMDAs) across the country, revealed widespread corruption in the public service of Ghana. Notable procurement related corrupt practices unraveled included influence peddling, inflating contract sums, payment for non-existing contracts, deliberate contract splitting, multiple payments for contracts, use of phantom vendors and misapplication of public funds. The study furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The effects of the whistleblower policy and the Treasury Single Account on manifestations of corruption in project planning and execution were exceptionally weak and restricted to tax evasion, falsely increasing the quantities of certified works, influence peddling, solicitation, and non-compliance with contracts. The findings additionally demonstrated that every one of the SACS is valuable as anti-corruption measures in project planning and execution, but increased access is the most useful system (Dza, et al, 2018;Aduwo, et al, 2020). Strategic measures that would altogether lessen manifestations of corruption in project planning and execution are increased information access, a cashless policy, due process, and political accountability.…”
Section: Logic Of Strategic Anti-corruption Systems (Sacs) and Their ...mentioning
confidence: 93%
See 1 more Smart Citation
“…The effects of the whistleblower policy and the Treasury Single Account on manifestations of corruption in project planning and execution were exceptionally weak and restricted to tax evasion, falsely increasing the quantities of certified works, influence peddling, solicitation, and non-compliance with contracts. The findings additionally demonstrated that every one of the SACS is valuable as anti-corruption measures in project planning and execution, but increased access is the most useful system (Dza, et al, 2018;Aduwo, et al, 2020). Strategic measures that would altogether lessen manifestations of corruption in project planning and execution are increased information access, a cashless policy, due process, and political accountability.…”
Section: Logic Of Strategic Anti-corruption Systems (Sacs) and Their ...mentioning
confidence: 93%
“…IPPIS protects public personnel against corrupt risks in the former system or manual salary calculation (Folorunso and Simeon, 2021). Public procurement due process controls public construction projects and fights corruption in project planning and procurement, promoting procurement integrity (Ebekozien, 2020;Dza, et al, 2018). No anti-corruption system is all-encompassing.…”
Section: Logic Of Strategic Anti-corruption Systems and Their Effects...mentioning
confidence: 99%
“…Dza et al expressed the view that despite the promulgation of the Public Procurement Act 663 (as amended), public procurement in Ghana is still fraught with abuse such as the use of phantom vendors, false claims, and presentation of fictitious invoices for payment. [34] Through connivance between staff and suppliers, incomplete orders not meeting required specifications are accepted, with receiving slips indicating that a full order with the required specifications was delivered.…”
Section: Procurement Store and Contract Irregularities Contained In mentioning
confidence: 99%
“…These studies established various lists of e‐procurement anti‐corruption factors in those countries. In Ghana, researchers (Addo, 2019; Dza et al, 2018; Eric & Dadzie, 2019; Osei‐Tutu et al, 2019; Ofori & Fuseini, 2020; Sarpong et al, 2018) have largely studied critical success factors (CSFs) that enhance the adoption of e‐procurement. Studies on the capability of e‐procurement to curb procurement fraud and corruption are non‐existent.…”
Section: Introductionmentioning
confidence: 99%